Why Are Opioid Prescribing Rates Higher in Rural Versus Urban Areas? - Alicia Sasser Modestino; Garry Young; Muhammad Mahmudul Hasan; Jiesheng Shi; Muhammad Noor E Alam (Institute of Labor Economics (IZA), 2025)
Patients in rural areas have higher rates of opioid use and overdose than those in urban areas that are linked to the greater prevalence and amounts of opioids prescribed. We merge individual claims data with county-level supply and demand factors to examine this relationship between geographical density and opioid prescribing. We find patients in rural areas are 10 percentage points more likely to receive an opioid prescription with about half of this differential attributable to the underlying health of the local population. A Blinder-Oaxaca decomposition reveals that roughly 80 percent of the remaining gap is explained by a combination of supply and demand factors. Allowing for the interaction of demand (e.g., working in a physically demanding occupation) and supply (e.g., healthcare delivery system) variables eliminates the gap. Our findings suggest several way states can reduce the gap in opioid prescribing between rural and urban areas, with possible downstream impacts on overdose and mortality.
Keywords: I14; I15; I18; 330; opioid; prescribing; density; health disparity; geography